2013
DOI: 10.1177/0267658313480154
|View full text |Cite
|
Sign up to set email alerts
|

Unfamiliar orthographic information and second language word learning: A novel lexicon study

Abstract: Recent research indicates that knowledge of words’ spellings can influence knowledge of the phonological forms of second language (L2) words when the first and second languages use the same orthographic symbols. It is yet unknown whether learners can make similar use of unfamiliar orthographic symbols. In this study we investigate whether native English speakers use orthographic tone marks to help them associate lexical tone with new L2 words? Native English speakers with no knowledge of Mandarin were assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 19 publications
5
100
3
Order By: Relevance
“…While a number of studies have demonstrated a facilitative effect of orthographic input for L2 learners (e.g., Escudero et al, 2008; Showalter and Hayes-Harb, 2013), others have found limited or no effect of orthographic input (e.g., Simon et al, 2010; Pytlyk, 2011; Escudero, 2015; Hayes-Harb and Hacking, 2015; Showalter and Hayes-Harb, 2015). Indeed, there are also circumstances where orthographic input can interfere with L2 phonological and lexical acquisition (Bassetti, 2006; Escudero and Wanrooij, 2010; Hayes-Harb et al, 2010; Mathieu, 2016).…”
Section: Orthographic Input and L2 Phonological Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…While a number of studies have demonstrated a facilitative effect of orthographic input for L2 learners (e.g., Escudero et al, 2008; Showalter and Hayes-Harb, 2013), others have found limited or no effect of orthographic input (e.g., Simon et al, 2010; Pytlyk, 2011; Escudero, 2015; Hayes-Harb and Hacking, 2015; Showalter and Hayes-Harb, 2015). Indeed, there are also circumstances where orthographic input can interfere with L2 phonological and lexical acquisition (Bassetti, 2006; Escudero and Wanrooij, 2010; Hayes-Harb et al, 2010; Mathieu, 2016).…”
Section: Orthographic Input and L2 Phonological Acquisitionmentioning
confidence: 99%
“…For example, a number of studies have found no effect of orthographic input in some cases where the graphemes and/or grapheme-phoneme correspondences are unfamiliar (e.g., Simon et al, 2010; Showalter and Hayes-Harb, 2013). Others have even found detrimental effects when the grapheme-phoneme correspondences of the L1 and L2 differ (Young-Scholten, 2002; Hayes-Harb et al, 2010; Hayes-Harb et al, submitted), or when the orthography is entirely unfamiliar (e.g., Mathieu, 2016).…”
Section: Orthographic Input and L2 Phonological Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a learning task with English nonwords including these vowels, Escudero, Hayes-Harb, and Mitterer (2008) showed that Dutch-native learners' ability to encode the /ae/-/ɛ/ contrast lexically was determined by the availability of a difference in spelling during the learning phase. Similarly, for native English speakers with no knowledge of Mandarin, even unfamiliar orthographic symbols, namely orthographic tone marks, help to associate auditory lexical tones with new L2 words (Showalter & Hayes-Harb, 2013). 15 Thus, for literate children and adults, orthography can support learning for more variable and transient phonological forms.…”
Section: Support Of Orthographic Representationsmentioning
confidence: 99%
“…The nonobject differed from one another in terms of visual similarity as well. This method is similar to that in previous studies of spoken language learning (Showalter & Hayes-Harb, 2013, 2015.…”
Section: Methodsmentioning
confidence: 82%